2022
DOI: 10.1515/med-2022-0428
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal hsa_circ_0000519 modulates the NSCLC cell growth and metastasis via miR-1258/RHOV axis

Abstract: This study aims to explore the function and mechanism of exosomal circ_0000519 in non-small cell lung cancer (NSCLC) development. Expression of circ_0000519, microRNA (miR)-1258, and Ras homolog gene family V (RHOV) in serum samples of NSCLC patients or cell lines were examined via quantitative reverse transcription-polymerase chain reaction and Western blotting. The function of circ_0000519 was evaluated through 5-ethynyl-2′-deoxyuridine (EdU) staining, colony formation, transwell, Western blotting, xenograft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The RHOV gene encodes a protein that may play a crucial role in the development and metastasis of lung cancer. The expression of the RHOV gene increases in the NSCLC ( Wang R. et al, 2022 ). Zhang et al (2021) suggested that the RHOV gene might influence the progression of lung adenocarcinoma by activating the JNK/c-Jun signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RHOV gene encodes a protein that may play a crucial role in the development and metastasis of lung cancer. The expression of the RHOV gene increases in the NSCLC ( Wang R. et al, 2022 ). Zhang et al (2021) suggested that the RHOV gene might influence the progression of lung adenocarcinoma by activating the JNK/c-Jun signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the RHOV gene increases in the NSCLC (Wang R. et al, 2022). Zhang et al (2021) suggested that the RHOV gene might influence the progression of lung adenocarcinoma by activating the JNK/c-Jun signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A worse prognosis is related to reduced expression of circLARP4 in NSCLC. Moreover, the capacity for SPCA1 cells to metastasize is inhibited by overexpression of the circLARP4 gene [ 118 ]. Another circRNA down-regulated in NSCLC that may prevent lymphatic metastasis is hsa_circ_0033155.…”
Section: Implication Of Exosomal Circrna In Lung Cancer Progressionmentioning
confidence: 99%
“…In addition to the factors mentioned above, we have summarized others derived from exosomes can serve as the potential regulators for EMT [20–24] and proliferation, migration and invasion [25–27,28 ▪ ,29–38,39 ▪▪ ,42] (Table 1).…”
Section: Tumour-derived Exosomes Promote Metastasis Through Regulatio...mentioning
confidence: 99%